Metodologiczne podstawy konstrukcji "Historii literatury niepodległej Polski" Ignacego Chrzanowskiego: w siedemdziesiątą rocznicę wydania książki = Methodical Principles of Construction of Ignacy Chrzanowski's "Lierary History of Intependent Poland" - Łojek, Mieczysław (1930-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article contains two parts. The first shows the way of scientific evolution of the author of Literary History. From his biography we know, that Mr. Chrzanowski after finishing his University studies worked as a scholar at Wroclaw under the guidance of Prof. Władysław Nehring and afterwards attended lectures by famous scientists in Berlin, as Mr. Alexander Brückner and Mr. Wilhelm Dilthey. Since 1894 Mr. Chrzanowski taught at private schools in Warsaw lecturing History of Polish Literature. It was a time of very intensive researches and till 1906, when he presented his text-book, he had puhlished more than 200 different reviews, articles and papers. The second part treats of the most important methodical principles of Construction of Literary History of Independent Poland
Keywords: Chrzanowski, Ignacy (186-1940); "Historia literatury niepodległej Polski"; literatura polska - historia